A Synthesis and Review of Medicinal uses, Phytochemistry and Pharmacological Properties of Maerua crassifolia Forssk. (Capparaceae) - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Maerua crassifolia Forssk. is an evergreen tree widely used as traditional medicine throughout its distributional range in the Sahel region, peninsular Arabia east to Pakistan, east and west Africa. This study is aimed at providing a critical review of medicinal uses, phytochemical and pharmacological properties of M. crassifolia. Documented information on medicinal uses, phytochemical and pharmacological properties of M. crassifolia was collected from several online sources such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as book chapters, books, journal articles and scientific publications obtained from the university library. The articles published between 1964 and 2020 were used in this study. This study revealed that the bark, fruit, leaf and twig infusion and/or decoction of M. crassifolia are mainly used as ethnoveterinary medicine, and traditional medicine for cephalalgia, headache, fever, malaria, wounds, skin infections, toothache and gastro-intestinal problems. Phytochemical compounds identified from the species include alkaloids, amino acids, betaines, cardiac glycosides, fatty acids, flavonoids, lignan glucosides, phenolics, quaternary ammonium compounds, saponins, steroids, tannins and terpenoids. The M. crassifolia extracts exhibited antibacterial, anti-diarrhoeal, analgesic, anti-inflammatory, antioxidant, antiplasmodial, antiprotozoal, antitrypanosomal, antipyretic and cytotoxicity activities. Maerua crassifolia should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.